КƏМЕЛЕТКЕ ТОЛМАҒАНДАРДЫҢ ҚЫЛМЫСТЫЛЫҒЫ: ЖАУАПКЕРШІЛІК ЖƏНЕ ЖАС ЕРЕКШЕЛІГІ (Journal of actual problems of jurisprudence, 2019)
The questions of changing criminal responsibility age of teens under 16 are considered